Selection strategy and modification of layer silicates for technical applications - Steudel, Annett (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Mineralogie und Geochemie, 2009)
In this study, samples were selected with respect to their layer charge and morphology. Sixteen bulk materials were pre-selected, which contained either swellable clay minerals or non-swelling clay minerals. One topic of this work was a comprehensive determination of layer and edge charge and exchange properties of clay minerals. A further topic in this study concerned the modification of swellable and non-swelling clay minerals with mineral acids, e.g., HCl and H2SO4.